The Bible in the Works of Thomas More : Part I: The Old Testament - Marc'hadour, Germain, (European History and Culture - Book Archive pre-2000., 1969)
A full list of Biblical quotes in More, with context and occasional comments on sources, parallels, etc. I. Old Testament II. The Four Gospels III. Acts, Epistles, Apocalypse IV. Elements of Synthesis V. Indexes, Supplements, Concordances The print edition is available as a set of five volumes (9789060041079).